The construction of a postgraduate student and supervisor support framework: Using stakeholder voices to promote effective postgraduate teaching and learning practice - Anderson, Malcolm; Mitchell, Brett; Northcote, Maria; Williams, Anthony; Petrie, Kevin; de Waal, Kayle; Carton, Janet; McLoughlin, Catherine; Lemke, Gina (Journal of University Teaching and Learning Practice, 2018)
This article outlines the design and development of a bespoke Research Training Support Framework, targeting the professional development needs of higher degree research (HDR) supervisors and their students, which was achieved by implementing Patton's (2011; 2012) utilisation-focused evaluation methodology (UFE). The primary research question was: What are the most suitable structures, components and content of an institutional framework to support Higher Degree Research (HDR) supervisors and their students at Avondale College of Higher Education? A mixed method design was used to gather data from students, academic staff and administrative staff using questionnaires, focus groups and interviews. Analyses of these data informed the Framework’s development along with previous research and advice from an advisory panel which comprised of national and international experts. Accordingly, the Framework was constructed around three core principles that served to guide the development of the Framework’s activities, processes and resources: 1) Welcoming research community, 2) The pedagogy of supervision and 3) Research development. The current version of the Framework has been designed to support postgraduate supervisors and students through the three key stages of students' most academically-focused stages of their postgraduate journeys namely; Getting started, Confirmation and Research and writing. The research-informed approach used to develop this contextually-relevant resource is particularly relevant to small higher education institutions, especially those wishing to focus on capacity development. Further research is currently being conducted to evaluate how the Framework is being used.